The concept of freedom among existentialists and Dr. Al-Bouti's criticism of them (an analytical and critical study) - Jalal, Prof. Dr. Ismail Mohamed Jalal; Ahmed, Sabah Abdulrahman Ahmed (Sulaimani Journal for Humanities, 2025)
The concept of freedom is a concept with different dimensions in terms of meaning, as everyone interprets it according to their own opinion and perception; therefore, its concept differs from one generation to another and from one era to another. For example, the scholars of the past defined it and expressed it as meaning facilitation and choice, and the scholars of the modern and contemporary eras discussed it and said that it means human freedom, which is the prevailing view in our day, and each group has their own opinion and understanding. The existentialist thinkers and philosophers said and expressed freedom as the essence of human material existence. In this research, this particular idea will be discussed, followed by the response of Sheikh Dr. Muhammad Saeed Ramadan Al-Buti - may God have mercy on him - and his criticism of it, until we arrive at the conclusion of the research: Is it true that freedom is the essence of human material existence or not?
Keywords: The concept of freedom; dimensions of freedom; development of the concept of freedom; freedom in Islamic thought